Cold saline irrigation of the renal pelvis during Radiofrequency Ablation of a central renal neoplasm: a case report - Morales Jose P; Sabharwal Tarun; Georganas Marios; Dourado Renato; Cahill Declan; Adam Andreas (Journal of Medical Case Reports, 2008)
Abstract Introduction Thermal destruction mediated by radiofrequency ablation (RFA) is gaining attention as an alternative treatment for patients with renal cell carcinoma (RCC), particularly in those who are not candidates for open surgery. Treatment of central tumours is occasionally associated with complications such as ureteric stricture, injury to the psoas muscle, haematuria and vascular laceration. Case presentation We have used infusion of cold saline during RFA, through a retrograde ureteric catheter with its tip in the renal pelvis, in a patient with a central renal tumour. Conclusion We believe this process to have successfully avoided the risk of thermal injury.